The Efficiency-Profitability Paradox: A Comparative Analysis of Digital and Conventional Customer Acquisition In Islamic Banking - Prayudha, Andra (Journal Of Middle East and Islamic Studies, 2026)
This study investigates the strategic dilemma faced by banking institutions in allocating resources between digital and conventional customer acquisition channels. Using a unique panel dataset from 38 Islamic bank branches, we analyze the comparative effectiveness of digital (Online Onboarding) and conventional (Payroll and Branch Registration) strategies on branch-level financial performance. Our findings reveal a significant efficiency-profitability paradox: a digital-dominant strategic orientation is associated with superior operational efficiency but does not translate into higher profitability. Furthermore, our analysis uncovers a critical nuance in conventional strategies through the discovery of inconsistent mediation: the institutional Payroll channel, while directly boosting margins, simultaneously erodes the funding structure, thus indirectly suppressing long-term profitability. This research challenges the prevailing assumption that transactional efficiency automatically leads to superior financial performance and highlights the often-overlooked, complex impacts of acquisition strategies on a bank's liability structure.